Penerapan Model Bisnis Inovatif dalam Kesuksesan Start-up Bukalapak di Industri E-commerce - Dwi Endah Desriani; Tata Sutabri (International Forum of Researchers and Lecturers, 2024)
Implementing innovative business models has been the key to success for many start-ups in the e-commerce industry. One example is the Bukalapak application which has achieved extraordinary success in a relatively short time. In this abstract, we will discuss the implementation of an innovative business model that is behind Bukalapak's success in facing fierce competition in the e-commerce industry. Bukalapak is an electronic trading platform that is one of the main players in the Indonesian market. In an effort to win competition in this tight industry, Bukalapak has implemented several innovative business models that differentiate itself from its competitors. This feature is different from other e-commerce platforms because it bridges gold trading directly between consumers without intermediaries. This provides additional flexibility and security for consumers who wish to invest or transact with gold. Bukalapak's success in implementing this innovative business model has been proven through the growth of active users of its application, increased transaction turnover, and increased market value. This success reflects the importance of implementing innovative business models in facing competition in the current e-commerce industry.